2017
DOI: 10.1017/s174392131700967x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and kinematic complexity of the very young star-forming region Serpens Main observed with ALMA

Abstract: The youngest low-mass protostars are known to be chemically rich, accreting matter most vigorously, and producing the most powerful outflows. Molecules are unique tracers of these phenomena. We use ALMA to study several outflow sources in the Serpens Main region. The most luminous source, Ser-SMM1, shows the richest chemical composition, but some complex molecules are also present in S68N. No emission from complex organics is detected toward Seremb 8N, which is the least luminous in the sample. We discuss whet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the Band 3 and Band 6 spectra of B1-b, B1-bN, Ser-emb 8 (N), and SMM3, COM emission features are absent at our detection sensitivity (see Table E.1), except for spatially extended CH 3 OH emission in Ser-emb 8 (N) which is related to the outflow (Tychoniec et al 2018a(Tychoniec et al , 2019. These sources are therefore excluded from further analysis and labeled as COM-poor sources.…”
Section: Spectral Modeling and Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In the Band 3 and Band 6 spectra of B1-b, B1-bN, Ser-emb 8 (N), and SMM3, COM emission features are absent at our detection sensitivity (see Table E.1), except for spatially extended CH 3 OH emission in Ser-emb 8 (N) which is related to the outflow (Tychoniec et al 2018a(Tychoniec et al , 2019. These sources are therefore excluded from further analysis and labeled as COM-poor sources.…”
Section: Spectral Modeling and Resultsmentioning
confidence: 69%
“…studied in detail by Kristensen et al (2010). Hull et al (2017) and Tychoniec et al (2018aTychoniec et al ( , 2019 observed several protostars in Serpens with ALMA, focusing on outflows. Interestingly, whereas Ser-emb 8 (N) hosts a high-velocity outflow, S68N only has a low-velocity outflow.…”
Section: Introductionmentioning
confidence: 99%